Perencanaan Pendidikan Di Kecamatan Cakung Jakarta Timur - Akifa Bakhitah Junaidi; Balqis Zulfa Ariqoh; Khusnul Abdul Qodar Romadhoni; Lacicya Tesalonika Damanik; Sekar Prabaswara Ayu Dewani; Sisi Khoirun Nisa (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
This study aims to analyze regional-based educational planning in Cakung District, East Jakarta. The research employed a qualitative descriptive method using observation, interviews, and documentation studies as data collection techniques. The findings reveal that Cakung District faces several educational challenges, including unequal educational facilities, the increasing number of school-age populations, and the need to improve educational infrastructure and teacher quality. The novelty of this study lies in its analysis of educational conditions based on administrative and socio-economic regional characteristics. Regional-based educational planning is considered capable of supporting the government in formulating more effective, equitable, and community-oriented educational policies. Therefore, this study contributes to the development of educational equity strategies in urban areas.